2019
DOI: 10.1001/jamaoto.2018.2875
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Health Care Costs and Utilization Associated With Untreated Hearing Loss Over 10 Years

Abstract: IMPORTANCENearly 38 million individuals in the United States have untreated hearing loss, which is associated with cognitive and functional decline. National initiatives to address hearing loss are currently under way.OBJECTIVE To determine whether untreated hearing loss is associated with increased health care cost and utilization on the basis of data from a claims database.DESIGN, SETTING, AND PARTICIPANTS Retrospective, propensity-matched cohort study of persons with and without untreated hearing loss based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
169
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 174 publications
(177 citation statements)
references
References 32 publications
6
169
0
2
Order By: Relevance
“…18 Under these frameworks, CI users underperform not because they struggle to perceive the information, which then impacts storage and retrieval, but because of differences in brain networks. We found that our participants correctly repeated 94.70% of the words, on average, across the first and second encoding trials on the stan- 38 Early detection and intervention of dementia could mitigate some of these accrued costs.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…18 Under these frameworks, CI users underperform not because they struggle to perceive the information, which then impacts storage and retrieval, but because of differences in brain networks. We found that our participants correctly repeated 94.70% of the words, on average, across the first and second encoding trials on the stan- 38 Early detection and intervention of dementia could mitigate some of these accrued costs.…”
Section: Discussionmentioning
confidence: 80%
“…Our results affirm the construct validity of the HI‐MoCA, which provides an alternate version to screen for dementia. Having an alternative format is important because of how common it is for individuals to have untreated HL, which is associated with greater health care costs and more hospitalizations . Early detection and intervention of dementia could mitigate some of these accrued costs.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing loss presents a significant global health burden as the 4 th leading contributor to years lived with disability (Vos et al 2016). Mounting evidence demonstrates significant associations between hearing loss, depression (Fellinger et al 2012), unemployment (Ruben 2015), risk for hospitalization (Genther et al 2013;Reed et al 2018) and cognitive decline and dementia (Lin et al 2011;Livingston et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss is independently associated with accelerated cognitive decline, dementia, falls, and reduced quality of life . Notably, recent studies have demonstrated that hearing loss burdens individuals, as well as the healthcare system, with increased healthcare utilization and spending …”
mentioning
confidence: 99%
“…7 Notably, recent studies have demonstrated that hearing loss burdens individuals, as well as the healthcare system, with increased healthcare utilization 8 and spending. 9 Importantly, the causal pathways between hearing and negative health outcomes may be modifiable via hearing care. Recent evidence suggests hearing aid use may mitigate the impact of hearing loss on cognitive decline, 10 healthcare costs, and utilization.…”
mentioning
confidence: 99%